Improving Adolescent Mental Health Through Experiential Learning During the COVID-19 Pandemic - Yulinda, Yulinda; Hufad, Ahmad; Permana, Elih Sudia; Robandi, Babang; Wahyudin, Uyu; Kamil, Mustofa (Kesmas, 2023)
Good adolescent mental health is a good investment for a country. During the COVID-19 pandemic, many adolescents did not carry out productive activities, possibly changing their mental health. Experiential learning facilitates metacognition, shapes adolescent cognitive processes, improves performance and problem-solving, and makes learning more meaningful and authentic. This study aimed to explore adolescents' mental health conditions and how experiential learning affects adolescents' mental health. Using a qualitative approach, the data collection through Google Forms questionnaire, FGDs, and interviews using the HEADSS instrument was conducted in September 2022 in Kebon Gedang Village, Batununggal Subdistrict, Bandung City, West Java Province, Indonesia. This study involved 73 adolescents aged 10-19 years as population. Still, only 59 participants were valid as a sample and willing to participate in making oil-based soap as a change for the monthly activity held by Integrated Health Care. The results showed that experiential learning by making oil-based soap at home improved adolescents' mental health by 80%. Following the learning objectives, this activity developed adolescents into healthy and economically successful individuals while significantly contributing to their community.